(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The effect of increasing pH value in the corrosion of iron alloy type (C1010) was studied in the presence of different pH solutions of sodium hydroxide dissolved in industrial water at 35ËšC and it was found that the corrosion rate of iron alloy was less at pH of 9.5 . This result was proved by measuring some thermodynamic parameters such as corrosion current and covered surface area that pertain to corrosion using weight loss electrical (Tafel plot ) methods . Also the effect of temperature on the rate of corrosion at ( 25ËšC , 35ËšC and 45ËšC ) at different pH was studied and it was found that the rate of corrosion is increased with increasing the temperature at the same pH.